Description of Blood Tablets Tablets Consumption of Girl Teenager in Tabanan - Cokorda Istri Mita Pemayun; Rini Winangsih; Kadek Sri Ariyanti (STIKES ADVAITA MEDIKA TABANAN, 2023)
Girl teenager are very susceptible to anemia because they lose a lot of iron during menstruation. The prevalence of anemia in young women is 32%. As an effort to prevent anemia, the government has implemented a program to provide Blood Supplementary Tablets (TTD) to young women aged 12-18 years through schools. The purpose of this study was to determine the knowledge of young women about iron tablets, explore experiences and factors that influence adolescent adherence in consuming iron tablets. The research design used is qualitative. The research was conducted in December 2022 at SMA Tabanan Regency. Data collection was carried out by interviewing through FGD. Informants in this study were 10 high school students in Tabanan Regency aged 12-18 years. For data validation, researchers used key informants, namely 5 parents of students, 1 teacher and 1 health worker. Data processing is done by means of triangulation. Results: Adolescent girls stated that they had taken iron tablets, but not regularly according to the government's recommended dose. Factors that cause adolescent non-adherence in consuming iron tablets are perception, parental support, teacher and school support, peer support and support from health workers. Continuous information is needed, including parents. There needs to be a media reminder so that young women regularly take iron tablets in accordance with the dose recommended by the government.